COLLABORATION OF WARUNG MADURA AND TOKO BASMALAH (STRATEGIC ALTERNATIVE TO REDUCE DEPENDENCE ON CHINESE ETHNIC DISTRIBUTORS IN PASURUAN) - Dewi Masita Dewi; Akhmad Syamsul Muniri; Nur Shofa Ulfiyati (LPPM IAI Dar Aswaja Rokan Hilir, 2026)
This Community Empowerment Program (CEP) aims to realize a strategic collaboration between Warung Madura and Toko Basmalah as a supply chain option to reduce the dependence of micro-business actors on large non-local distributors (Chinese ethnic distributors) in Pasuruan. Through a participatory mentoring approach and strengthening of the economic institutions of the people, this program has succeeded in directing the shift of the supply chain of Warung Madura to Toko Basmalah. The impact is an increase in average turnover of 15% and a profit margin of up to 10% within three months of implementation. This collaboration shows the potential of the historical block of the local economy as initiated by Antonio Gramsci, namely the consolidation of the community economy as a counterbalance to the dominance of hegemonic capitalism. This CEP concludes the importance of the continuity of institutional strengthening, support for affirmative policies of the local government, and the use of digital technology to strengthen the competitiveness of the people's economy.